Die Gräberfelder von Sedment im Neuen Reich : materielle und kulturelle Variation im Bestattungswesen des ägyptischen Neuen Reiches - Franzmeier, Henning. (Probleme der Ägyptologie, 2017)
In Die Gräberfelder von Sedment im Neuen Reich , Henning Franzmeier presents and reassesses the complete results of the previously only partially published excavations undertaken by W.M.F. Petrie and G. Brunton in the New Kingdom cemeteries of Sedment, Middle Egypt, from 1920 to 1921. Through his research, Franzmeier has expanded the corpus of known New Kingdom tombs at Sedment from about 50 to more than 250, including burials of high-ranking officials, and identified a wide range of previously unknown objects. Presenting the development of an important provincial cemetery, this publication provides a valuable contribution to our understanding of New Kingdom Egyptian funerary archaeology and, as a case study, highlights the potentials of reassessing the results of past excavations.